PENGUKURAN DAN APLIKASI KLINIK THROMBIN ACTIVATABLE FIBRINOLYSIS INHIBITOR - Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Cross regulation of coagulation and fibrinolysis plays an important role in preserving a balanced hemostatic process. These process are exquisitely regulated and protect the organism from excessive blood loss or excessive fibrin deposition. Identification of ThrombinActivatable Fibrinolysis Inhibitor (TAFI) as an inhibitor of fibrinolysis and one of the main intermediates between coagulation andfibrinolysis, greatly improved our understanding of cross regulation of coagulation and fibrinolysis. As TAFI is an enzyme that is activatedby thrombin generated by the coagulation system, its activation is sensitive to the dynamics of the coagulation system. This review willdiscuss the role of TAFI and characterize it with respect to its activation, regulation, and clinical application.